Cephalometric evaluation of maxillary retrognathism cases treated with FR-3 appliance. - (:unkn) unknown (My University, 1993)
The purpose of this investigation was to evaluate the efficiency of the FR-3 appliance on functional Cl III malocclusion cases. A total of 45 functional Cl III cases were chosen from a general clinic intake of which 25 were treated with the FR-3 appliance and 20 were untreated and were taken as a control group. Patients that were treated with FR-3 had the following characteristics: Cl III with maxillary deficiency; functional anterior cross-bite; absence of anterior open-bite; patients in mixed dentition. The mean age in the treatment group was 8.4 years 8.8 years in the control group. The observation period was one year for both groups. The results were as follows: Sagittal forward growth stimulation was not observed in the maxilla. Mandibular growth was redirected in the vertical direction. The SNB angle decreased in that the mandible rotated downward and backward. The ANB angle increased. There was an increase in total and lower anterior facial height and reduction in the overbite. Another skeletal change observed was the increase in the cranial flexure angle. Improved dental results were a significant amount of overjet increase and a decrease in the IMPA. There was also a beneficial effect on the soft tissue profile.